PERUBAHAN SOSIAL MASYARAKAT NEGERI HENA LIMA PASCA BENCANA BANJIR WAE ELA DI KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - M. Syafin Soulisa (IAIN Ambon, 2019)
ABSTRACT Intention of this research is to depict the condition of social change of society of Hena Lima pasca of disaster of floods of Wae Ela Yar 25 July 2013. Data collecting done by observation, interview and documentation. Research informan is society of victim of disaster of floods of Wae Ela Yar, elite figure, governmental of Hena Lima. this Research Result that first; the happening of social life change of society of pasca of disaster of floods Wae Ela marked with the change of at regional layout of resident housing, social relation of neighbour and consanquinity progressively go away the, change also at education systems, change of at social class status of society, individual attitude. [Both/ second]; Economic life change of society namely immeasurable progressively it society living among others as building labour, merchant, and other service work. Affect the change cause the society progressively individualism, estranged public relations progressively and more egoist having the character of and also feel depend on relief fund floods. Keywords: Social Change, Hena Lima, Floods